O papel da mídia na expansão do medo e consolidação da demanda punitiva - Silveira, Antônio Paulo Soares Lopes da (2016)
This study aims to carry out an analysis of fear and how it can influence society from a media coverage of social facts which most affect citizens, the news that more thrill. It proposes an analysis of fear from individual and collective points of view, trying to narrow a conceptualization of this emotion, inherent to all men, relating the process of thinking as a binary matter of emotion-reasoning. A relationship between risk and violence, this qualified as what society understands as crime, carried out to determine the beacons of what is feared, the risk of crime and, in consequence, the indiscriminate search for security. Thus, it presents criminal law as the rescue mechanism to achieve this desired security, safety above all things and needs, with the background of a fear that numbs the search for other solutions. The media issue is addressed from the theory of agenda-setting, also by analyzing a sensationalist journalism prism, which influences the entire construction of a culture and a society.